SEORANG PENDERITA DENGAN LEUKEMIA MIELOID KRONIK DAN MIELOMA MULTIPEL - Suega, Ketut (journal of internal medicine; Vol. 11, No. 3 September 2010)
Chronic Myeloid Leukemia (CML) and Multiple Myeloma (MM) are two chronic progressive diseases characterized by neoplastic proliferation of myeloid cell and monoclonal plasma cell. Chronic myeloid leukemia was recognized as a distinct entity, associated with massive splenomegaly and as ! rst malignant disease found to be constitutively associated with spesi! c cytogenetic abnormality the Philadelphia oncogene. Whereas MM is frequently recognized by monoclonal protein production and either difuse osteoporosis or lytic bone lesion. Clinical manifestation are consequence of marrow in! ltration of plasma cells, production of M protein in blood or urine and immune de! ciency. Coincidence of these two diseases in one particular patient is a very rare occasion. Herewith we reported a woman 42 years old Balinese presented of abdominal enlargement without symptom of bone pain, anemic syndrome. After complete examination supporting by ! nding on bone marrow examination this patient ! nally diagnosed of having chronic phase of CML and MM stage IIIB as well. Treatment was given with hydroxy urea and other supported measures and we planned to continue with melphalan and prednisone. There were no clear explanation for this condition whether it occur concomitantly or one disease follow with the other. Several reports found that in quite similar occasion Melphalan was the agent of suspected with induced secondary malignancy. Others also found twenty MDS patient together with lymphoid malignancy and plasma cell. Tanaka et.al., noted that a more satisfactory explanation is that both disorders are from malignant transformation of a precursor cell capable of differentiating into both lymphoid and myeloid lines. In our case more likely that CML concomitantly found with MM because there were no previous history of having chemotherapy nor radiotherapy.
Keywords: chronic myeloid leukemia, multiple myeloma, coexistence